ANTESEDEN KETERLIBATAN PEMBELIAN PRODUK PREMIUM MODE BUSANA DI INDONESIA DENGAN MENGGUNAKAN PEMODELAN PLS SEM - Siti Hindah Widiyastuti; Purwoko Purwoko; Aftoni Susanto; Zunan Setiawan; Salamatun Asakdiyah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study seeks to gain a better understanding of the involvement of purchasing premium fashion products. Therefore, it considers consumer attitudes towards premium product engagement by investigating how fashion awareness and materialism serve as the main antecedents of purchasing involvement in premium fashion products. This study aims to test the model and adapt it from the involvement of purchasing premium products. This study uses purposive sampling, an online survey method is used based on 270 questionnaires that can be collected. The results of the study reveal that fashion awareness and materialism affect the involvement of purchasing premium fashion products. The practical implication is that there must be successful communication with the fashion-conscious and materialistic millennial consumers in order to develop strategies that are consistent with consumer values ​​and lifestyle appeals. This paper develops a comprehensive model that examines and analyzes the relationship between fashion awareness, materialism, and purchase involvement in premium fashion products.